Answer:
I have already answered this in your last question:)
Answer:
g(x) = x^2 -6x +9
Step-by-step explanation:
A function f(x) translated right h units and up k units will become ...
g(x) = f(x -h) +k
You want the function f(x) = x^2 to be translated right h=3 units, so it will become ...
g(x) = f(x -3) = (x -3)^2
g(x) = x^2 -6x +9
Answer:
(2, 2)
Step-by-step explanation:
just say it was mental math
Answers:
a = 1/3
b = -6
c = 7
======================================================
Explanation:
The terms of the given expression rearrange to which is now in standard form (the exponents decrease when moving from left to right).
We can see that
a = 1/3
b = -6
c = 7
after matching that with the ax^2+bx+c form.
After 5 days
You can solve this by plugging 5 in.
-3(5)+42 = 27
4(5)+7 = 27
They have the same result.